A new 1 μm laser crystal Nd:Gd2SrAl2O7: growth, thermal, spectral and lasing properties. (6th March 2018) - Yuan, Feifei; Liao, Wenbin; Huang, Yisheng; Zhang, Lizhen; Sun, Shijia; Wang, Yeqing; Lin, Zhoubin; Wang, Guofu; Zhang, Ge
Abstract: Nd:Gd2 SrAl2 O7 crystals were grown by the Czochralski technique; thermal, spectral and laser properties were investigated in detail. The average thermal expansion coefficients along a - and c -axis are 12.6 × 10 −6 K −1 and 14.9 × 10 −6 K −1, respectively. At room temperature, the thermal conductivities are 4.98 and 5.24 W (m −1 * K −1 ) along the a - and c -axis, respectively. The absorption cross sections at 808 nm are 13.7 × 10 −20 cm 2 with a FWHM of 3.3 nm for π -polarization and 11.84 × 10 −20 cm 2 with a FWHM of 3.4 nm for σ -polarization. The emission cross sections at 1080 nm are 15 × 10 −20 cm 2 and 12.7 × 10 −20 cm 2 with a FWHM of about 5.1 nm and 12.5 nm for π - and σ -polarization, respectively. The fluorescence lifetime for the 4 F3/2 → 4 I11/2 transition was fitted to be 118 µ s. Pumped by a fiber-coupled 808 nm laser diode, the maximum 1.55 W continuous-wave laser output at 1.08 µ m was achieved with a slope efficiency of 30.5%. All the results show that Nd:Gd2 SrAl2 O7 crystal is a promising laser material.